Tourist Kelong Bintan Black Coral Business Strategy During COVID-19 Pandemic - Muhammad Rizki; Octojaya Abriyoso; Eka Kurnia Saputra; Samsiyah Samsiyah; Lia Putri; Tati Tati (Institute of Computer Science (IOCS), 2022)
The fast-mutating COVID-19 virus requires business actors in Indonesia to adapt quickly, not least for business actors in the tourism industry such as Bintan Black Coral which is located in Bintan Regency, Riau Islands Province. This study aims to identify the strengths, weaknesses, opportunities, and threats faced by Bintan Black Coral and formulate strategies that can be implemented while operating during the COVID-19 pandemic. This study adopted a qualitative method using interviews and observations as data collection techniques. The data were then analyzed using the IFE, EFE, and SWOT analysis matrixes. The results show that Bintan Black Coral is in relatively good condition internally and is relatively able to take advantage of opportunities and minimize the threats it faces. The results of the SWOT analysis reveal strategies that can be adopted by Bintan Black Coral during the COVID-19 pandemic as well as strategies that can be implemented continuously